MORFOLOGI DAN KLASIFIKASI TANAH PADA FORMASI PENIRON BAHAN INDUK ANDESIT PIROKSEN DI DESA PAGEDONGAN, BANJARNEGARA - Veti Nur Aisyah; Mohammad Nurcholis; Djoko Mulyanto (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Rock formation as parent material in Pagedongan Village, Banjarnegara influences the properties of the soil formed. The purpose of this research was to identify the morphology and soil classification according to USDA Taxonomy, National Soil Classifications, and World Reference Base for Soils. This study uses a survey method by determining observation points based on a rock formation, namely Peniron Formation, with pyroxene andesite as parent material for observing soil morphology, physical and chemical of soil in the field, then laboratory analysis included soil texture, bulk density, organic C, soil pH H2O and KCl, exchangeable cations K, Ca, Mg, Na, CEC, and base saturation. The results showed that the soil developed in the Peniron Formation with pyroxene andesite as parent material had morphology with diagnostic horizons of umbric epipedon and argillic endopedon. The results showed that the soil classification according to USDA Taxonomy is Typic Palehumults Isohyperthermic, according to National Soil Classifications is Podsolics Ortoxic, and according to World Reference Base for Soils is Loamic Abruptic Alfisols.